Lecturers’ Non-Verbal Communication during the English Lesson: Student Perceptions Study - Karman, Karman; Nurfadillah Nurchalis (Eduvelop: Journal of English Education and Development, 2024)
To create effective teaching and learning, it is essential to comprehend students' perceptions. It assists lecturers in customizing their teaching strategies to fit the requirements and preferences of their students. This adaptation contributes to more effective instructional strategies, more student engagement, and a more successful learning experience for everyone involved in the classroom. The research focused on exploring the perceptions of nonverbal communication employed by English lecturers among first-semester students enrolled in the Islamic education program at STAIN Majene. The study used a descriptive quantitative design which involved 140 students across four classes, with 75 volunteered as samples. A questionnaire was used to collect data on various nonverbal communication cues, and descriptive quantitative analysis was conducted to gain insights. The results demonstrate that students have a positive perception of the use of nonverbal communication by English lecturers. It implies that students prefer dynamic and positive learning environment through appropriate use of this communication method in English lessons.